Right ventricular outflow tract histology post-stenting and in-stent stenosis - Sudesh Prabhu; Siddhant Mehra; Shravan Kanaparthi; Shreesha Shankar Maiya; Sruti Rao (Wolters Kluwer Medknow Publications, 2022)
The right ventricular outflow tract (RVOT) stenting is used for the treatment of Fallot-type lesions when not amenable to complete correction or when surgical palliation carries a substantial risk. Despite the increasing clinical application, there is a lack of data that describe the RVOT morphology after stenting. This article elucidates post-RVOT stenting and in-stent stenosis, which is thought to be a zonal phenomenon, in this case, predominantly occurring proximally, in the portion of the stent apposing the RVOT infundibulum.